Contribuição para o estabelecimento de critérios de outorga para aproveitamentos hidrelétricos - Marcus Vinicius Cristelli Moura (2006)
This paper introduces a methodology for analyzing and establishing criteria for water rights for hydropower generation. Nowadays, in Brazil, the instrument of water rights serves as an important tool for managing water resources. Its application to the hydropower sector is becomingincreasingly necessary in order to provide adequate operation of hydropower plants, as well as to manage multiple water use within the watershed and in the reservoir. The current non application of the instrument of water rights for hydropower plants may cause additional risk for energy production, as a result of diffuse watershed consumptivewater use, which might have been ignored in the reservoir water balance.The Brazilian government, through its water management agency (Agência Nacional de Águas ANA), and through some state agencies, such as those located in the states of Bahia, Rio Grande do Sul and São Paulo, are already using this tool as a criteria for water rights. However, there is still a lack of a set of systematic technical criteria for evaluating water rights, in the context of the countrys large remaining hydropower potential, and there is, also, an urgent need for specific regulations.